METHODS OF ORGANIZING LABORATORY TRAINING IN THE COURCE FOR MECHANICS USING MODERN INFORMATION TECHNOLOGIES (Web of Teachers: Inderscience Research, 2025)
In our paper we examine the problem of increasing the effectiveness of training specialists in educational institutions. It is shown that the professional readiness of students as a personal quality and an essential prerequisite for the effective activity of a specialist, the successful performance of their duties, the correct use of knowledge and experience, helps to quickly adapt to working conditions and promotes further professional development.